Advances in High–Speed, High–Power Photodiodes: From Fundamentals to Applications - Qingtao Chen; Xiupu Zhang; Mohammad S. Sharawi; Raman Kashyap (Applied Sciences, 2024)
High–speed, high–power photodiodes play a key role in wireless communication systems for the generation of millimeter wave (MMW) and terahertz (THz) waves based on photonics–based techniques. Uni–traveling–photodiode (UTC–PD) is an excellent candidate, not only meeting the above–mentioned requirements of broadband (3 GHz~1 THz) and high–frequency operation, but also exhibiting the high output power over mW–level at the 300 GHz band. This paper reviews the fundamentals of high–speed, high–power photodiodes, mirror–reflected photodiodes, microstructure photodiodes, photodiode–integrated devices, the related equivalent circuits, and design considerations. Those characteristics of photodiodes and the related photonic–based devices are analyzed and reviewed with comparisons in detail, which provides a new path for these devices with applications in short–range wireless communications in 6G and beyond.